Exploring the public's perception towards crowdsourced crime reporting - Wan Abu Bakar, Wan Mohamad Luqman; Solemon, Badariah (2017)
This paper presents the results of an exploratory study conducted to investigate the public perception towards crime information shared by the crowds.Information required for the study was obtained through a survey, self-administered questionnaires distributed to the crowds in public areas including shopping mall, food court, mosque, and institutes of higher learning in Selangor, Malaysia as well as those posted on an online survey website.The results from 139 valid responses show that the crime rate is perceived to have been increasing and crime information is often shared on social media, mobile messaging applications, mobile applications and online newspapers.However, most respondents do not show high confidence and trust levels with the crime related information shared in these technologies particularly from mobile messaging application.Also, majority of the public believe that the current protection level in their community by the police force show no significant difference than before.Findings from this survey is very important in designing future crime prevention technologies that provide insight to the public with crime related information, which would lower their chances of being targeted.